Early variation of quick sequential organ failure assessment score to predict in-hospital mortality in emergency department patients with suspected infection. (August 2019) - Lemachatti, Najla; Ortega, Mar; Penaloza, Andrea; Le Borgne, Pierrick; Claret, Pierre-Géraud; Occelli, Céline; Truchot, Jennifer; Dumas, Florence; Feral-Pierssens, Anne-Laure; Andrianjafy, Héry; Beaune, Sebastien; Yordanov, Youri; et al.
Abstract : Background: The quick sequential organ failure assessment (qSOFA) score showed good prognostic performance in patients with suspicion of infection in the emergency department (ED). However, previous studies only assessed the performance of individual values of qSOFA during the ED stay. As this score may vary over short timeframes, the optimal time of measurement, and the prognostic value of its variation are unclear. The objective of the present study was to prospectively assess the prognostic value of the change in qSOFA over the first 3 h (ΔqSOFA = qSOFA at 3 h−qSOFA at inclusion). Patients and methods: This is an international prospective cohort study conducted in 17 EDs in France, Belgium, and Spain. From November 2016 to March 2017, patients with a suspected infection and a qSOFA score of 2 or higher were included and followed up until death or hospital discharge. qSOFA was measured at inclusion, 1 h and 3 h. Primary end point was in-hospital mortality, truncated at 28 days. Results: Of 534 recruited patients, 512 were included in the analysis. The qSOFA was improved at 3 h (ΔqSOFA < 0) in 287 (55%) patients. Overall in-hospital mortality was 27%: 44% when ΔqSOFA greater than 0, 36% when ΔqSOFA = 0, and 18% when ΔqSOFA less than 0. A positive ΔqSOFA was independently associated with reduced in-hospital mortality (adjusted hazard ratio of 0.48, 95% confidence interval: 0.34–0.68). After modeling qSOFA kinetics in the first 3 h, there was a significant difference in adjusted slopes between patients who died and those who survived (0.15, 95% confidence interval: 0.09–0.22, P < 0.001). Conclusion: In patients with suspected infection presenting to the ED with a qSOFA of 2 or higher, the early change in qSOFA is a strong independent predictor of mortality. Abstract : Supplemental Digital Content is available in the text.